Curative Effect of Synchronous Functional Training of Neuromuscular Eelectrical Stimulation on Patients with Functional Ankle Instability - Ziwen PEI; Zhizhong GENG; Gongli YAN; Danyang LI; Jian CHEN (康复学报)
Objective:To observe the effects of synchronous functional training of neuromuscular electrical stimulation (NMES) on patients with functional ankle instability (FAI).Methods:A total of 50 FAI patients treated in the hospital of Wuhan Sports University were randomly assigned to NMES group and control group by random number table method, with 25 cases in each group. Both groups performed conventional functional exercise including warm up activities, resistance training of the muscle groups around the ankle joint, balance training and stretching exercise after the training. The NMES group received NMES on peroneal muscles (PM) of affected side while performing muscle strength training and balance training for eight weeks, 20 minutes each time, three times a week. The PM muscle strength of patients was evaluated with Peak Torque of Evertor (E-PT) measured by the isokinetic system in eccentric/concentric mode before and after the treatment, the improvement of posture stability was assessed by the Y Balance Test (YBT), and the self-reported ankle function were evaluated by Cumberland ankle instability tool (CAIT).Results:There were no significant differences in E-PT, YBT score, CAIT score and PAI score between the two groups before the treatment (P> 0.05). After eight weeks of treatment, the E-PT, YBT score, and CAIT score in both groups were significantly increased, and PAI score was significantly decreased compared with those before the treatment (P< 0.05). After eight weeks of treatment, the E-PT, YBT score and CAIT score in the NMES group were significantly higher than those of the control group (P< 0.05), PAI score was significantly lower than that of the control group (P< 0.05).Conclusion:The synchronous functional training of NMES can significantly enhance the evertor strength, posture stability, and self-perceived ankle function in FAI patients. The curative effect of the method is better than that of only conventional functional exercise, and the method is worthy of clinical promotion and application.